209k views
0 votes
Which expression is equivalent to 3(x – 6) + 5(x – 4)? A. 8x – 10 B. 15x2 – 38x C. 8x – 38 D. 9x – 22

2 Answers

2 votes

The answer is C.

3(x-6)+5(x-4) = 3•x+3•-6 = 3x-18 and 5•x+5•-4 = 5x-20

3x-18+5x-20

3x+5x = 8x and -18+-20 = -38

Which gives you...

8x-38

User Zans
by
6.2k points
3 votes

Answer:

C. 8x – 38

Explanation:

he equation.

All the options have the parenthesis solves, with all the numbers distribute, so first, you need to do that.


3(x – 6) + 5(x – 4)=


(3*x) - (3*6) + (5*x) -(4*5)=

now, solve what you can


3*x=3x\\3*6=18\\5*x=5x\\4*5=20

And put it all together


3x - 18 + 5x - 20

You can link the X therms and the no X terms


(3x + 5x) =8x\\(-18 - 20) =-38

And the final equation is: 8x - 38

User Chopmo
by
5.5k points